2001
DOI: 10.1055/s-2001-15134
|View full text |Cite
|
Sign up to set email alerts
|

The Silyloxy-Cope Rearrangement of Syn-Aldol Products: Evolution of a Powerful Synthetic Strategy

Abstract: Enantiomerically pure 1,5-hexadienes incoporated into a silylated aldol structure undergo rapid, clean, high-yielding and highly stereoselective Cope rearrangements. The 7-oxo-2-enimides thus obtained are formally the products of a γ-1,4-selective addition of a metal dienolate to an α,β-unsaturated aldehyde − a transformation which current methodology can not accomplish directly and stereoselectively. They have proved to be very useful synthetic intermediates en route to highly substituted oxygen and nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…The alcoholysis requires a catalyst because alcohols are not generally sufficiently nucleophilic to attack hydrosilanes. Strongly nucleophilic or electrophilic catalysts can be used [2], and a limited number of transition metal complexes [4][5][6][7][8][9][10]. It has been found that chloroplatinic acid, even in minute amounts, is an extremely potent catalyst, but few examples have been reported in the literature [11].…”
Section: Introductionmentioning
confidence: 99%
“…The alcoholysis requires a catalyst because alcohols are not generally sufficiently nucleophilic to attack hydrosilanes. Strongly nucleophilic or electrophilic catalysts can be used [2], and a limited number of transition metal complexes [4][5][6][7][8][9][10]. It has been found that chloroplatinic acid, even in minute amounts, is an extremely potent catalyst, but few examples have been reported in the literature [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since rate accelerations were achieved by the introduction of silyloxy groups into Cope systems, 17 an attempt to also facilitate the cycloreversion started from silylether 7 which was subjected to thermal conditions up to 300 1C. However, only the Cope rearrangement product 8 was isolated after in situ hydrolysis (Scheme 2).…”
mentioning
confidence: 99%
“…Our observations are particularly noteworthy when contrasted with the corresponding oxy-anion version, which when substituted with electron withdrawing groups such as esters and amides in the 4-position succumbs to the unwanted retro-aldol pathway . In the context of realizing asymmetric rearrangement goals with such substrates, Schneider, Nakai, Black, and Davies have demonstrated that protection of the troublesome 3-hydroxyl with a silyl or benzoate group allows the oxy-Cope rearrangement to proceed albeit at very high temperatures in addition to two steps (protection/deprotection) being added to the overall synthetic sequence.…”
Section: Introductionmentioning
confidence: 82%